Challenges South African youth face in education and their quest to eradicate issues of the past (Alternate Horizons, 2021)
The youth of South Africa today face many challenges in their daily lives. The majority of South Africa's population is made up of youth- people aged between 15 and 35 years old.  The youth in South Africa face challenges such as crime, unemployment, poverty, and most importantly unequal opportunities in education. These challenges should not be present in the daily lives of South African youth, especially since it has been over two decades since South Africa’s first democratic elections. The challenges that are faced in the education system is explored and solutions are suggested to help end the chain of poverty.
Keywords: South Africa; youth; education; poverty